Spontaneous Subdural Hematoma associated with Meningioma : Two case reports - Acharya, Samir; Prajapati, Ramesh; Shrestha, Bishal; Malla, Samridha; Gurung, Pritam; Pant, Basant (Nepal Journal of Neuroscience, 2024)
Introduction: Spontaneous subdural hematoma rarely presents with a hyper vascular or malignant tumor but even less frequently in a benign tumor like meningioma. We encountered two cases with spontaneous subdural hematoma associated with benign meningioma. Case Description: A 47-year-old Asian woman presented with severe headache and forgetfulness, initiated 3 months before, with no other complaints, denying any previous head trauma. Head computed tomography revealed a chronic left hemisphere subdural hematoma for this issue she underwent burr hole and evacuation of hematoma 1 month before. However her symptoms was not relieved and her magnetic resonance imaging of brain showed left frontal lesion , suggestive of meningioma. Surgical treatment was performed. The tumor was histologically confirmed as a transitional meningioma grade I. After surgery, no neurological deficits were registered, and headache subsided. Similarly, second case, a 56-year-old woman presented with complaints of severe headache for 6 hours. There is no history of seizure like activities, any previous history of head trauma. On examination, no neurological deficits noted. Computed Tomography (CT) of head showed a hyper dense extradural lesion with acute subdural lesion on left hemisphere. MRI brain revealed well defined extra axial round to oval lesion measuring 3.1 X 3.5 X 2.5 cm with areas of heterogeneous enhancement of the left parietal parasagittal area .She underwent left parietal craniotomy and en-bloc tumor resection done. Post operatively there was no neurological deficits and she was discharged on 5th post-operative day. Conclusions: As we could not identify any other cause for the subacute subdural hematoma, hemorrhage from the meningioma was the most probable cause. Although meningiomas are commonly benign according to their histological traits, they can lead to spontaneous bleeding and cause neurologically unstable condition. Therefore, meningiomas need to be considered as a cause of spontaneous subdural hematoma if radiologically suspicious, which should be reflected by proper management for a positive outcome.